Reflections on Mises’ Human Action - Smith, Vernon Lomax (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
The author applies the Experimental Economics to analyze some of the postulates of Mises in Human Action. He seeks to demonstrate, using the postulates of Experimental Economics, that the spontaneous order, operating through the institutions of property rights, displays the desirable characteristics that Austrians claimed. This power of demonstration is, to the author, much more attractive than the appeal to reason, especially emphasized by Mises.